Learning Writing Through Reading Text - Damanik, Emeliya SukmaDara (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2017)
This paper shares about the ideas in learning writing through reading the text. It is an alternative way to o develop student’s mind in writing. by reading the text, the student is not only get the information but also the ideas so that they can resulted the new product. Some ideas which has been discussed in this study, it can be applied to the teacher, student, lecturer or instructor involved in reading and writing pedagogy.